A new approach to characterization of asphaltene. Issue 14 (17th July 2016) - Behbahani, Taraneh Jafari; Tayyebi, Shokoufe
ABSTRACT: Asphaltene is the fraction of crude oil which is soluble in toluene but insoluble in light hydrocarbon solvents such as pentane or heptanes. In this work, a new approach has been proposed to account critical properties of asphaltene, and the proposed approach was verified using experimental data reported in the literature. The results show that the proposed approach correlates more accurately the critical properties of asphaltene data and is in agreement with data reported in the literature with an average absolute deviation of 6.7%. Therefore, the correlations obtained from this proposed approach resulted in a good agreement with data which show a significant improvement in comparison with the previous models in the available literature.